(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Female bonding draws the attention of some theorists who analyze and examine women‘s relationships and the different challenges facing them. Toni Morrison studied women‘s identities and relationships and their impact in the community. They analyze women‘s experiences related to race, class and gender, and how women develop strategies that allow them to survive. They foreground how black women connect in order not only to heal the pain resulting from these misfortunes but also to provide themselves with comfort and security. Morrison reflects, In developing a theory of female friendship, I seek to represent the world as women imagine it could be, and as many women have created it. Feminist theory must take into account the forces maintaining the survival of women as well as those that maintain the subordination of women. A theory of female friendship is meant to give form, expression, and reality to the ways in which women have been for our Selves and each other.